Identification and synthesis of mycalol analogues with improved potency against anaplastic thyroid carcinonia cell lines - Cutignano, Adele; Seetharamsingh, B.; D'Angelo, Daniela; Nuzzo, Genoveffa; Khairnar, Pankaj V.; Fusco, Alfredo; Reddy, D. Srinivasa; Fontana, Angelo (Journal of Natural Products, 2017)
The marine metabolite mycalol (1) has a specific inhibitory activity on cells of anaplastic thyroid carcinoma (ATC), a very aggressive and rare cancer that does not have effective conventional therapy. In this study, we describe six new related analogues (2-7) that differ in the length of the terminal alkyl residue and the presence of acetate or 3S-hydroxybutyrate (3S)-3HB as a substituent at C-19. Despite the structural' analogies, some of the new members were significantly more-cytotokic than 1 on cell lines,derivecl from human ATC. Structures inclusive of the 2'R,3R,4S,7R,8S,19R absolute configuration were asigned to 2-7 on the basis of detailed spectroscopic analysis, synthesis of different isomers, and application of ECD and Mosher's methods. This work led to the identification of mycal61-578 (3) as the most potent analogue, with an IC50 of 2.3 mu M on FRO cells:

Insect-repellent and mosquitocidal effects of noreremophilane- and nardoaristolone-based compounds - Handore, K. L.; Kalmode, H. P.; Sayyad, S.; Seetharamsingh, B.; Gathalkar, G.; Padole, S.; Pawar, P. V.; Joseph, M.; Sen, A.; Reddy, D. S. (ACS Omega, 2019)
Here, we disclose novel mosquito-repellent synthetic hydrindanes based on noreremophilanes and nardoaristolone B which show increased activity against adult females of Aedes aegypti. The noreremophilanes and nardoaristolone B with hydrindane skeleton are structurally related to nootkatone with decalin skeleton, a well-studied natural product extracted from a grape fruit. Out of our library of compounds synthesized based on the noreremophilanes and nardoaristolone B scaffolds, NDS-100598 (compound 20) exhibits higher repellent and knock-down effects at a very low concentration (0.25 mg/cm2), while a few analogues showed considerably enhanced activity compared to racemic nootkatone. This is the first report documenting insect-repellent and knock-down activity of the noreremophilanes class of compounds.